Maturity at harvest and postharvest quality of summer squash - Massolo, Juan Facundo (2019)
The objective of this work was to evaluate the influence of harvest at maturity on the composition, quality, and postharvest life of zapallito squash (Cucurbita maxima var. zapallito). Fruit were harvested at three developmental stages-small, medium, and large, with 30, 70, and 90±10-mm diameter, respectively-and were stored at 0 and 5°C for 26 days and, then, at 20°C for 2 days. The following parameters were determined: respiration, firmness, color, chlorophyll content, carotenoids, sugars, acidity, phenolic compounds, antioxidants, decay, mass loss, and chilling injury (CI). Small light-colored squashes were more prone to dehydration and decay. Delaying harvest markedly reduced fruit carotenoid contents, acidity, and respiration rate; however, it did not affect firmness nor sugar content. Chlorophyll showed an increasing trend during fruit development. Small squashes had 100% higher levels of phenolic compounds and antioxidants than medium and large fruit, but were more sensitive to CI. No differences for CI susceptibility were observed between medium and large fruit. The quality of small, medium, and large squashes remained acceptable for 12, 19, and 26 days at 5C, respectively, plus 2 days at 20C.